A Study on Organizational Clarity and Its Impact on Employer Branding In Automobile Companies in Chennai City - Parvin, A. Sajitha; Dawood, Dr.Ayub Khan (International Journal of Advanced Science and Technology, 2019)
Organisational climate has a major influence on organisational effectiveness through its impact on individual motivation and job satisfaction.Factors that are included in climate are individual autonomy,organisational clarity, degree of structure imposed upon the people, reward orientation and warmth and support. Organisational clarity is defined as the comprehension an employee has about the organisation’s vision, purpose, mission, strategy, opportunities, challenges, priorities and competitive reality.The aim of the study is to evaluate the employees’ perceptions on organisational clarity in Automobile Industry and to test the impact of organisational clarity on employer branding.A descriptive study was done on 366 employees of Automobile Companies. The finding of the study revealed that the employees requires more clarity with respect to grievance procedure, work environment and stress management programmes. Their clarity perception on openness of the environment, Job Security and internal reporting system was lesser compared to other job related and technology related perceptions. It was found in the study that age, experience and designation have significant influence on the perception of organisational clarity. The study also revealed that the clarity perception of Junior Engineers/Engineers’and employees’ with less than 30 years of age was lesser compared to other employees. At the same time the positive effect of organisational clarity was significantly stronger among employees with higher work experience compared to employees with low work experience. The study also discoveredthat the perception of employees on organisational clarity influences employer brandingsignificantly. Clarity in HR policies and Clarity with problem solving mechanism have more than 79% correlation with employer branding. Hence the companies need to take more steps to communicate the HR polices and problem solving mechanism more clearly to its employees.